No is not enough [compact disc, unabridged] : resisting Trump's shock politics and winning the world we need - Klein, Naomi, 1970- (Blackstone Audio, 2017)
Journalist Naomi Klein explains that Trump is not an aberration but a logical extension of the worst and most dangerous trends of the past half-century.